Cloning and Characterization of a New Chitosanase From a Deep-Sea Bacterium Serratia sp. QD07 - Zheng, Qiuling; Meng, Xiangjun; Cheng, Mingyang; Li, Yanfeng; Liu, Yuanpeng; Chen, Xuehong (Frontiers in Microbiology, 2021)
Chitosanase is a significant chitosan-degrading enzyme involved in industrial applications, which forms chitooligosaccharides (COS) as reaction products that are known to have various biological activities. In this study, the gene csnS was cloned from a deep-sea bacterium Serratia sp. QD07, as well as over-expressed in Escherichia coli, which is a new chitosanase encoding gene. The recombinant strain was cultured in a 5 L fermenter, which yielded 324 U/mL chitosanases. After purification, CsnS is a cold-adapted enzyme with the highest activity at 60°C, showing 37.5% of the maximal activity at 0°C and 42.6% of the maximal activity at 10°C. It exhibited optimum activity at pH 5.8 and was stable at a pH range of 3.4–8.8. Additionally, CsnS exhibited an endo-type cleavage pattern and hydrolyzed chitosan polymers to yield disaccharides and trisaccharides as the primary reaction products. These results make CsnS a potential candidate for the industrial manufacture of COS.